2017
DOI: 10.1097/mnh.0000000000000290
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid antagonists in chronic kidney disease

Abstract: MRAs have a clear role in further reducing very high albuminuria when used with other renin-angiotensin system blockers; however, hyperkalemia is a limiting factor for the use of MRAs. Use of the new potassium binder patiromer has facilitated the use of MRAs in CKD, and novel nonsteroidal MRAs are currently being tested in advanced CKD outcome trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 52 publications
0
10
0
1
Order By: Relevance
“…Han et al previously demonstrated that spironolactone prevents diabetic nephropathy through an anti-inflammatory mechanism in type 2 diabetic rats [ 24 ]. Randomized studies confirmed that the addition of MRAs to a renin–angiotensin system (RAS) blocker reduced albuminuria resulting from diabetic or nondiabetic causes [ 25 , 26 ]. Additionally, the use of spironolactone alone was similarly effective to the use of spironolactone and losartan combination in reducing albuminuria [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al previously demonstrated that spironolactone prevents diabetic nephropathy through an anti-inflammatory mechanism in type 2 diabetic rats [ 24 ]. Randomized studies confirmed that the addition of MRAs to a renin–angiotensin system (RAS) blocker reduced albuminuria resulting from diabetic or nondiabetic causes [ 25 , 26 ]. Additionally, the use of spironolactone alone was similarly effective to the use of spironolactone and losartan combination in reducing albuminuria [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…84 There are no long-term data from RCTs on clinical benefits. In addition, side effects, particularly hyperkalemia and acute reversible reduction in eGFR, 85 are a concern when added to background therapy with an ACEi or ARB or diuretic, particularly among patients with eGFR <45 ml/min per 1.73 m 2 . 86 Thus, blocking aldosterone may be particularly useful in patients with resistant hypertension without a history of high potassium, and GFR >45 ml/min per 1.73 m 2 .…”
Section: No Dosage Adjustment Necessary Poorly Removed By Hemodialysismentioning
confidence: 99%
“…Mineralocorticoid receptor antagonists (MRAs) have a track record of benefit in cardiovascular complications of DKD, that is, heart failure risk reduction, and of efficacy in reducing albuminuria and treating resistant hypertension . Thus, with the advent of novel non‐steroidal MRAs with generally less hyperkalaemia risk, there is a renewed commitment, to investigate their effect on both slowing DKD progression and reducing cardiovascular risk in diabetes …”
Section: Introductionmentioning
confidence: 99%